The bees of the genus Centris Fabricius, 1804 described by Theodore Dru Alison Cockerell (Hymenoptera: Apidae) - Vivallo, Felipe (European Journal of Taxonomy, 2020)
In this paper the primary types of Centris bees described by the British entomologist Theodore Dru Alison Cockerell deposited in the Natural History Museum (London) and the Oxford University Museum of Natural History (Oxford) in the United Kingdom, as well as in the United States National Museum (Washington), American Museum of Natural History (New York), the Academy of Natural Sciences of Drexel University (Philadelphia), and in the California Academy of Sciences (San Francisco) in the United States were studied. To stabilize the application of the name C. lepeletieri (= C. haemorrhoidalis (Fabricius)), a lectotype is designated. The study of the primary types allow proposing the revalidation of C. cisnerosi nom. rev. from the synonymy of C. agilis Smith, C. nitida geminata nom. rev. from C. facialis Mocsáry, C. rufulina nom. rev. from C. varia (Erichson), C. semilabrosa nom. rev. from C. terminata Smith and C. triangulifera nom. rev. from C. labrosa Friese. Centris bakeri syn. nov., C. bimaculata carrikeri syn. nov., C. fusciventris matoensis syn. nov., C. heterodonta syn. nov. and C. elegans grenadensis syn. nov. are proposed as a new junior synonyms of C. varia, C. claripennis Friese nom. rev., C. caurensis, C. dentata Smith and C. elegans Smith, respectively. Centris ruae is withdrawn from the synonymy of C. transversa Pérez and proposed as a new junior synonym of C. nitida Smith. In addition, a lectotype for C. buchholzi Herbst (= C. wilmattae) is designated. Information on the repository of the lectotype of C. lepeletieri and images of most primary types studied here are also provided.